Genetic variation for yield characters of F1 hybrids in Indian mustard (Brassica juncea L.) (Journal of Oilseed Brassica, 2026)
Twenty F1 hybrids generated in 5×5 diallel and evaluated during 2017-18 to study the genetic variability for seed yield and other important quantitative traits. Analysis of variance revealed significant differences for hybrids for all characters studied indicating sufficient genetic variability for all the characters. The variance due to parents were highly significant for all the characters except days to first flowering, primary branches/ plant, number of secondary branches/ plant, days to maturity, plant height and the variance due to crosses were highly significant for all the characters except plant height. Variances due F1’s were significant for all characters except plant height, and seeds/ siliquae. Phenotypic correlation coefficient revealed that seed yield/ plant had significant positive correlation with number of siliquae/ plant followed by number of primary branches/ plant and biological yield/ plant. Path coefficient analysis revealed that biological yield/ plant had highest positive direct effect with seed yield/ plant followed by days to 50% flowering, number of primary branches/ plant and harvest index.